(untitled) (Research, Society and Development, 2020)
The study was conducted at Gashua, Yobe State. The weather condition of the area during summer is so terrible to the extent that the majority of inhabitants are searching for ice blocks or cold water to drink in other to feel a bit comfortable. In the school, both teachers and students were not comfortable during summer and winter seasons and these made teaching and learning processes boring. Therefore, the study is aimed at assessing the assimilation and academic performance of students during the vsummer and winter seasons. A random selection of past examination record sheets of students in Yusad secondary school, Gashua was used, and information on their academic performance for summer and winter season were obtain from senior secondary one and two (SS1 and SS2) classes. Ten student record books were selected at random for their academic performance on the subject area of biology. Their scores of the academic performance records were subjected to a descriptive statistics where mean, standard deviation was calculated and Z-test was determined. The results of this study revealed that the summer and winter seasons do not affect the assimilation and results reveals that the academic performance of students varies between - 0.58 in SS1 to - 0.72 in SS2 which means that the summer and winter seasons had no influence on the assimilation and performance of students but might cause inconvenience, unfavorable, disturbance and unsuitable conditions for teaching and learning processes.